Human and mouse perforin are processed in part through cleavage by the lysosomal cysteine proteinase cathepsin L - Konjar, Špela (Blackwell Science Inc, 2010)
The pore-forming protein perforin is synthesized as an inactive precursor in natural killer (NK) cells and cytotoxic T lymphocytes (CTLs), and becomes active when a short C-terminal peptide is cleaved within acidic lysosome-like cytotoxic granules. Although it was shown more than a decade ago that this cleavage is pH dependent and can be inhibited by the generic cysteine cathepsin inhibitor E-64d, no protease capable of processing the perforin C terminus has been identified. Neither is it known whether a single protease is responsible or the processing has inbuilt redundancy. Here, we show that incubation of human NK cells and primary antigen-restricted mouse CTLs with the cathepsin L (CatL) inhibitor L1 resulted in a marked inhibition of perforin-dependent target cell death and reduced perforin processing. In vitro, CatL preferentially cleaved a site on full-length recombinant perforin close to its C terminus. The NK cells of mice deficient in CatL showed a reduction but not a complete absence of processed perforin, indicating that cysteine proteases other than CatL are also able to process perforin. We conclude that granule-bound cathepsins are essential for processing perforin to its active form, and that CatL is an important, but not exclusive, participant in this process.